CLINICAL FEATURES OF THE COURSE OF ERYSIPELAS OF THE SKIN AT THE PRESENT STAGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Streptococcal infections continue to be among the most pressing health problems in all countries of the world. Purpose of the study: To describe the clinical features of the course of erysipelas in the Samarkand region. Materials and methods of the study: Analysis of the incidence of erysipelas was carried out in the period from 2014-2019. according to a retrospective analysis of medical records of patients diagnosed with “Essipelas” according to ICD-A46.0, who were hospitalized in the regional clinical infectious diseases hospital of the city of Samarkand. Conclusions. Contacts with patients with chronic tonsillitis are equally common for patients with both primary and recurrent erysipelas. Separation of patients plays a key role in recurrent erysipelas. Proper organization of clinical examination of patients after hospital treatment prevents relapse of the disease.